2018
DOI: 10.1080/17518253.2018.1440324
|View full text |Cite
|
Sign up to set email alerts
|

Modification strategies of TiO2 for potential applications in photocatalysis: a critical review

Abstract: TiO 2 has received tremendous attention owing to its potential applications in the field of photocatalysis for solar fuel production and environmental remediation. This review mainly describes various modification strategies and potential applications of TiO 2 in efficient photocatalysis. In past few years, various strategies have been developed to improve the photocatalytic performance of TiO 2 , including noble metal deposition, elemental doping, inorganic acids modification, heterojunctions with other semic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
180
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 387 publications
(202 citation statements)
references
References 77 publications
1
180
0
1
Order By: Relevance
“…To overcome limitations and drawbacks, many researches have suggested to employ hybrid systems which combine two or more of these different modification techniques [40]. The advantages and disadvantages of the main modification strategies along with the performance results from the most important CO 2 photoreduction studies are summarized in Tables 1 and 2 below [19,26,37,[88][89][90]. Further details on the pros and cons of the mentioned TiO 2 surface modification techniques are discussed in the following individual Sections 3.1-3.5…”
Section: Titanium Dioxide: Synthesis and Surface Modification Strategmentioning
confidence: 99%
“…To overcome limitations and drawbacks, many researches have suggested to employ hybrid systems which combine two or more of these different modification techniques [40]. The advantages and disadvantages of the main modification strategies along with the performance results from the most important CO 2 photoreduction studies are summarized in Tables 1 and 2 below [19,26,37,[88][89][90]. Further details on the pros and cons of the mentioned TiO 2 surface modification techniques are discussed in the following individual Sections 3.1-3.5…”
Section: Titanium Dioxide: Synthesis and Surface Modification Strategmentioning
confidence: 99%
“…Moreover, the substitutional and interstitial doping of impurities from the feed water can significantly affect the particle size of the prepared TiO 2 NPs [24,47]. For instance, the high Ca (large atomic radius when comparing Ti) content (see Table 2) in A-TiO 2 crystal might have contributed towards the enhancement of crystal size through substitutional doping [32]. Table 2 demonstrates the elemental composition of the prepared A-Residue and A-TiO 2 from EDX analysis along with the estimated BET specific surface area (S BET ).…”
Section: Physicochemical Properties Of the Prepared A-tio2mentioning
confidence: 99%
“…Castro and Durán [53] reported that Ca doping on TiO 2 at a very low concentration (<3 wt.%) could reduce the band energy gap of TiO 2 and enhance the photodegradation of methyl orange under solar irradiation. However, the doped Ca of substantial amount can act as recombination site for e -/h + pair generated during photodegradation (see Figure 1) and might cause a reduced level of photoactivity [32]. Similarly, Wang et al [54] illustrated that a certain amount (2 atomic%-4 atomic%) of Cl as the dopant in TiO 2 could activate TiO 2 under visible light, and the extent of light absorption within the UV range can get reduced, so as the photoactivity.…”
Section: Photocatalytic Activity Of Prepared A-tio 2 Npsmentioning
confidence: 99%
See 1 more Smart Citation
“…Os mecanismos de ação dos POAs são diversos, mas destacam-se aqueles capazes de formar agentes altamente oxidantes (radicais livres) e que apresentam maior eficiência para degradação destes contaminantes (Boczkaj & Fernandes, 2017). Neste aspecto, a fotocatalise heterogênea tem sido amplamente investigada, uma vez que semicondutores fotoativos apresentam capacidade para geração destes radicais livres (Humayun, Raziq, Khan, & Luo, 2018).…”
Section: Aplicações Ambientais Da Lâmpada Hg-mdel Em Poasunclassified